The effect of depression at work towards employee performance at Malaysian anti corruption commision Kuantan Pahang / Nur Fazeera Yasmin Yusoff - Yusoff, Nur Fazeera Yasmin (Faculty of Business and Management, 2018)
This study was conducted to determine the effects of job depression towards employee in organization which also effect on their work performance. The researcher focuses on level of depression, stress and social environment towards employee to know how those factor make effect on their work performance. Method used by the researcher to study this research is by a questionnaire. The questionnaire were given to all workers which is 55 respondents at Malaysian Anti Corruption Commission (MACC) in Kuantan, Pahang. The duration of the study is between March 2017 until December 2017. Descriptive statistics such as means, standard deviation, and percentage were used to describe the research questions of the study. The data was analyzed using SPSS software. The result of this study shows that the level of depression, stress and social environment of the employee in MACC Pahang were not effect their work performance. They can handle the depression at their workplace. Somehow, they are suggested to develop more positive social environment and improve their social interaction and skills learning.